Hungary : Economic Policies for Sustainable Growth. (Occasional Papers; Occasional Paper ;, 1998)
Economic developments in Hungary during 1995-97 illustrate one of the most remarkable cases of macroeconomic adjustment in Europe over the last decade. Several momentous steps in the integration of the Hungarian economy with the rest of Europe and the industrial countries community took place. In May 1996, Hungary acceded to the OECD; in July 1997, it was invited to join NATO; and in the same month, the European Commission recommended that EU start membership talks in near future. Reducing inflation, maintaining a sustainable external position, and allowing growth of the private sector will require the continuation of the prudent fiscal policies that have characterized 1995-97.